RADI-29. BIOLOGIC SUBTYPES OF BREAST CANCER BRAIN METS AS A PREDICTOR OF LOCAL CONTROL AFTER STEREOTACTIC RADIOSURGERY. (12th August 2019) - Salgado, Lucas Resende; Smith, Andrew; Cohen, Alexandra; Tseng, Tzu-Chi; Lin, Jung-Yi; Moshier, Erin; Green, Sheryl; Germano, Isabelle
Abstract: INTRODUCTION: Brain metastases (BM) are diagnosed in approximately 15% of breast cancer (BC) patients. Biologic subtype is predictive of loco-regional recurrence following breast conserving therapy and/or mastectomy with the highest risk in the ER-/PR-/HER2- (TN) subtype. The aim of this study is to determine whether biologic subtype is predictive of local control (LC) in BC patients with BM treated with Stereotactic Radiosurgery (SRS). MATERIALS/METHODS: All patients underwent LINAC-based SRS at our institution. Patients were subdivided into three biologic subtypes: ER+/Her2- (Luminal), Her2+, and TN (Basal). Kaplan Meier method was used to estimate the overall survival (OS). Cox proportional hazard model was used to analyze association of local failure (LF) with biologic subtypes. This is an IRB-approved single center retrospective study. RESULTS: 108 BC BM in 50 consecutive patients were included in this study with a median follow up of 11.1 months. The median disease-specific GPA was 2.0, and all patients received systemic chemotherapy and/or hormonal therapy. The 12 month LC rates for the entire cohort were 85%, 87%, 49% for Luminal, Her2+ and Basal, respectively, with a significantly shorter LC for the basal sub-type (p=0.014). The 12 month OS rates were 83%, 88%, 80% for Luminal, Her2+ and Basal, respectively with a no significant difference in OS among the subgroups. 24% of the lesions were treated with salvage whole brain radiation therapy. CONCLUSIONS: This study shows that in BC patients with BM treated with SRS, biologic subtype impacts LC but not OS. Consideration of radiation treatment intensification or altered fractionation to improve LC may be indicated for the TN subtype. Further multi-center studies are necessary to corroborate our results.